2019
DOI: 10.1155/2019/7909137
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Schistosomicidal Activity of the Alkaloid-Rich Fraction from Ruta graveolens L. (Rutaceae) and Its Characterization by UPLC-QTOF-MS

Abstract: Schistosomiasis is a neglected tropical disease that affects million people worldwide, mostly in developing countries. Ruta graveolens (Rutaceae) is a plant used in folk medicine to treat several diseases, including parasitic infections. In this study, we reported the in vitro schistosomicidal activity of the R. graveolens extract (Rg) and its active fraction (Rg-FAE). Also, the characterization of Rg-FAE by UPLC-ESI-QTOF-MS analysis and its in vitro antileishmanial activity against Leishmania braziliensis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Although PZQ is effective in chronic infection, it has a limited effect on granulomatous lesions and against juvenile Schistosoma [3–5] . Additionally, the concerns over the emerging PZQ‐resistance development [6] have renewed interest in the search for new antischistosomal agents, particularly from natural sources [1,7,8] . Among natural compounds, chalcones have been shown promising antischistosomal activities [1,5,9,10] …”
Section: Introductionmentioning
confidence: 99%
“…Although PZQ is effective in chronic infection, it has a limited effect on granulomatous lesions and against juvenile Schistosoma [3–5] . Additionally, the concerns over the emerging PZQ‐resistance development [6] have renewed interest in the search for new antischistosomal agents, particularly from natural sources [1,7,8] . Among natural compounds, chalcones have been shown promising antischistosomal activities [1,5,9,10] …”
Section: Introductionmentioning
confidence: 99%
“…Parasites were kept for 48 h (37°C, 5% CO 2 ), and their viability was assessed via microscopic readout (Leica Microsystems, Wetzlar, Germany) [ 34 ]. Next, samples presenting antischistosomal activity were tested at lower concentrations, as described above, and each experiment was performed at least three times [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mammalian Vero cells (African green monkey kidney fibroblast) used in this study were obtained from the American Type Culture Collection (ATCC CCL-81; Manassas, VA) and provided by Instituto Butantan (São Paulo, Brazil). Cytotoxicity of the samples was determined using the MTT assay [ 35 ]. The values of cytotoxic concentration reducing 50% of viable cells (CC 50 ) were obtained using GraFit Version 5 software.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, plants are considered a natural source for desired secondary metabolites such as phenolic compounds, flavonoids, tannins, terpens, essential oils, alkaloids and other bioactive compounds. The presence of these bioactive compounds is responsible for the antioxidant activity of Ruta tuberculata Forssk, which helps in the prevention against several types of diseases including preventing the development of chronic illness related to oxidative stress by inhibiting or reducing free radicals’ production, such as ROS and NOS [ 8 , 9 ]. Furthermore, the anti-inflammatory, anti-ulcer [ 2 , 5 ], neuroprotective and anti-cholinesterase activities of these bio-compounds were widely screened and documented [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have reported the antioxidant, anti-inflammatory, anti-ulcer, hepatoprotective and anti-Alzheimer effects of Ruta plants [ 1 , 2 , 3 , 13 ]. In fact, the pharmacological proprieties of Ruta species could be attributed to the presence of diverse chemical classes of secondary biocompounds, including coumarine, alkaloid derivatives [ 8 , 14 ], essential oils [ 11 , 15 ], lignanes [ 16 ], polyphenols and flavonoids [ 3 , 17 , 18 ]. Based on the previous literature, there are no studies reported on phenolic characterization of the aerial parts of R. tuberculata growing in Algeria and their pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%